2017
DOI: 10.1016/j.jclepro.2016.06.080
|View full text |Cite
|
Sign up to set email alerts
|

Environmental impacts of food consumption in Europe

Abstract: Food consumption is amongst the main drivers of environmental impacts. On one hand, there is the need\ud to fulfil a fundamental human need for nutrition, and on the other hand this poses critical threats to the\ud environment. In order to assess the environmental impact of food consumption, a lifecycle assessment\ud (LCA)-based approach has been applied to a basket of products, selected as being representative of EU\ud consumption. A basket of food products was identified as representative of the average food… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
258
1
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 419 publications
(293 citation statements)
references
References 22 publications
5
258
1
5
Order By: Relevance
“…The use of food proxies, instead of the actual food items that are consumed, has strengths and weaknesses. The use of proxy products has been applied in several consumption-oriented LCA studies to specifically assess the impacts of certain representative foods consumed in a specific region (Notarnicola et al 2017). For example, Muñoz et al (2010) assessed annual Spanish food consumption based on LCA studies available in the literature on food proxies for Spanish food purchased by households, catering, restaurants, and institutions.…”
Section: Description Of the Research Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The use of food proxies, instead of the actual food items that are consumed, has strengths and weaknesses. The use of proxy products has been applied in several consumption-oriented LCA studies to specifically assess the impacts of certain representative foods consumed in a specific region (Notarnicola et al 2017). For example, Muñoz et al (2010) assessed annual Spanish food consumption based on LCA studies available in the literature on food proxies for Spanish food purchased by households, catering, restaurants, and institutions.…”
Section: Description Of the Research Methodsmentioning
confidence: 99%
“…Eberle and Fels (2016) selected some proxies for their study based on their share of the product group and on data availability. Furthermore, in Notarnicola et al (2017), a basket of food products was identified as a representative of average European food and beverage consumption, in order to assess the environmental impacts of food consumption in Europe. According to Notarnicola et al (2017), the selected food proxies reflected the relative importance of the products in terms of mass and economic value.…”
Section: Description Of the Research Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, the scope of study was restricted to the food products portfolio. Agriculture production is identified as the main hotspot in the environmental footprint of food products and as the primary single driver of biodiversity loss, with quite a strong scientific consensus (Colomb et al, 2015b;Kok et al, 2014;Notarnicola et al, 2017;Steinfeld et al, 2006). So, the scope of the quantitative assessment was circumscribed to the food portfolio of product (PoP) at the agricultural production phase.…”
Section: Scope and Functional Unitmentioning
confidence: 99%
“…For instance, consuming meat has a much larger ecological footprint than consuming legumes and grains (Notarnicola et al, 2017). As a consequence, it might be much more sustainable to satisfy protein requirements via legumes and grains than via meat.…”
Section: Environmental Sustainabilitymentioning
confidence: 99%